Management of Ureters Involved in Inguinal Hernias (Translation: The University of Toledo Journal of Medical Sciences, 2018)
Background: The presence of a ureter in a hernia sac presents a unique surgical challenge and can increase the likelihood of ureteral injury at the time of surgery as they are often not identified pre-operatively. Here we present our institutional experience and thorough systematic review in order to provide guidance on the urologist’s role in this situation.Materials and Methods: A PubMed and Medline search was conducted to identify relevant literature published in the year 2000 or later. Case reports and case series in the English language were included using terms “ureter and hernia”, “herniated ureter”, “ureteral hernia”, inguinal hernia and ureter”.Results: The presence of a ureter in an inguinal hernia sac is an uncommon finding. When present, many are not identified pre-operatively, which places the patient at risk for ureteral injury during herniorrhaphy.Patients with ureters contained in their inguinal hernias, that were identified pre-operatively or intra-operatively and not injured, recovered well. Post-operative imaging, when performed, showed stabilization or improvement of hydronephrosis and a more normal course of the ureter. One case reported the identification of ureteral involvement post-operatively after injury, which resulted in worsened renal function and required a re-operation.Conclusions:The presence of a ureter in an inguinal hernia can be differently managed. The primary goal should be avoidance of injury intra-operatively.